The rapture eaudiobook Countdown to the rapture series, book 3. - LaHaye, Tim (Before They Were Left Behind, 2006)
The final prequel will have the Rapture three-quarters of the way through the book and then following characters such as Irene and Raymie (and others) up to heaven and being able to see events in the Tribulation from heaven's perspective. The book will alternate between focusing on events on earth immediately after the Rapture (covering lots of things the authors wished they could have covered in the original volumes) and focusing on characters in heaven and how they view the chaotic events on earth.